Reconstructing the metamorphic evolution of the Araçuaí orogen (SE Brazil) using in situ U–Pb garnet dating and P–T modelling. (19th April 2021) - Schannor, Mathias; Lana, Cristiano; Nicoli, Gautier; Cutts, Kathryn; Buick, Ian; Gerdes, Axel; Hecht, Lutz
Abstract: The Araçuaí orogen of SE Brazil consists of a suite of deformed, metamorphosed, and partly migmatitic sedimentary rocks and granitoid batholiths that predominantly formed during collision of the São Francisco and Congo cratons during West Gondwana assembly in the late Neoproterozoic. While widespread anatexis and a prolonged magmatic record are well‐established, insufficient information exists about the extensive exposure of metamorphic rocks along the Araçuaí orogen. Combining information from a wide range of these metamorphic rocks is essential to reconstruct mountain‐building processes and heat sources that operate in convergent tectonic settings. New petrographic observations, mineral chemistry, and phase equilibria modelling were used to constrain peak metamorphic conditions of amphibolite facies metasedimentary rocks from the central domain of the orogen at 580–620°C and 7–9 kbar. We applied in situ low‐U (<1 µg/g) garnet U–Pb geochronology, which yielded ages in the range of 590–565 Ma, interpreted as the timing of bulk garnet growth during prograde metamorphism, and consistent with previously established monazite ages for the peak metamorphic event. Metamorphic zircon ages of c . 630 Ma are related to a cryptic terrane accretion event prior to the orogeny, whereas garnet U–Pb ages record the main orogenic event as revealed by disequilibrium rare earth element partitioning between the two minerals. A compilation of our results with previously reported metamorphic conditions defines a clockwise P–T evolution for the Araçuaí orogeny, characterized by slow burial to depths of 26–30 km, followed by nearly isothermal decompression from ~10 to 6 kbar. Substantial differences of peak temperatures in various domains of the orogen are consistent with the presence of different protoliths in the crustal sections. The higher concentration of heat‐producing elements (HPEs) in lithologies from the anatectic domains may have triggered partial melting of metasedimentary rocks. This suggests that HPEs were a significant heat source for crustal reworking during West Gondwana convergent tectonics.